2018
DOI: 10.21831/hsjpi.v4i2.10321
|View full text |Cite
|
Sign up to set email alerts
|

Faktor determinasi profesionalisme guru

Abstract: Penelitian bertujuan untuk mengetahui pengaruh (1) kualifikasi pendidikan terhadap profesionalisme guru, (2) sikap inovatif terhadap profesionalisme guru, (3) etos kerja terhadap profesionalisme guru, dan (4) pengaruh kualifikasi pendidikan, sikap inovatif dan etos kerja secara simultan terhadap profesionalisme guru IPS SMP di Kabupaten Gowa. Penelitian ini merupakan penelitian kausal-komparatif yang bersifat ex post facto. Penelitian menggunakan populasi sebesar 119 orang guru IPS. Pengumpulan data menggunaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
1
5
0
1
Order By: Relevance
“…The survey results show that at least teachers have met the minimum standard of academic qualifications. These results are in accordance with the results of study showing that educational qualifications, innovative attitudes and ethos have an effect on increasing teacher professionalism [22].…”
Section: Personal/self-developmentsupporting
confidence: 92%
See 2 more Smart Citations
“…The survey results show that at least teachers have met the minimum standard of academic qualifications. These results are in accordance with the results of study showing that educational qualifications, innovative attitudes and ethos have an effect on increasing teacher professionalism [22].…”
Section: Personal/self-developmentsupporting
confidence: 92%
“…This is proved by the significant value [21]. The other research declared that the education qualification, innovative attitude and ethos affected to the improvement of teacher professionalism [22]. Setiawan found that education level and teaching experience correlated to teacher's creativity, but not the income [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educators or teachers are learning facilitators who escort students to the learning goals (Lie, 2013). As learning facilitators, teachers are required to have the willingness of lifelong learning, to develop innovative attitudes, and to have high work ethics for those three are proven giving positive effects towards teachers' professionalism (Syamsuriyanti & Sukirno, 2018). On the other hand, the finding also shows that less creative and innovative learning at classes needs to be obliviated and shifted to more effective learning.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, teachers need to keep doing a lifelong learning, develop innovative attitudes, and have a high work ethic. Based on the results of the study, the three last mentioned things have proven to have a positive infl uence on teacher professionalism (Syamsuriyanti & Sukirno, 2018).…”
Section: Introductionmentioning
confidence: 92%